Can cultural relativism affect the international protection of human rights? - Ferreira Dias, J. (Revista Jurídica Portucalense, 2024)
This paper examines the influence of cultural relativism on the international protection of human rights, addressing the complex interplay between universal human rights standards and cultural diversity. Cultural relativism, which posits that human rights should be interpreted within the context of a specific culture, often conflicts with the principle of universality upheld by international human rights instruments. This tension raises critical questions about the applicability and enforcement of human rights norms across diverse cultural landscapes. By analyzing concrete cases and theoretical perspectives, the paper explores how cultural relativism can challenge and enrich the discourse on human rights. It highlights the potential for cultural relativism to undermine universal human rights protections by justifying practices that violate fundamental rights. Conversely, it argues that a nuanced understanding of cultural contexts can enhance the legitimacy and effectiveness of human rights interventions. The paper concludes by advocating for a balanced approach that respects cultural diversity while upholding the core human rights principles, emphasizing the need for dialogue and adaptability in the international human rights regime. The paper examines how instruments like the African Charter on Human and Peoples' Rights offer pathways to reconcile universal human rights with cultural diversity through adaptive frameworks.